A Survey of a Study on the Reasons Responsible for Student Dropout from the Bachelor of Science Programme at Indira Gandhi National Open University - Fozdar, Bharat Inder; Kumar, Lalita S.; Kannan, S. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
This paper presents a report on students who decided to drop out of the BSc programme offered by Indira Gandhi National Open University (IGNOU). This study was designed to determine the reasons leading to students’ decisions to withdraw from the programme. Identified in this study are nine major reasons for dropouts. Results of this study lead to several suggestions for improving current instructional and delivery strategies of IGNOU’s BSc Programme. Following such suggestions could help to reduce students’ dropout rate for this particular programme through implementation of timely interventions at different critical stages of their learning journey.